Some Remarks on Technological Process of Tartessian Pottery - Michał Krueger (EXARC, 2018)
The main aim of this research is to recognise some aspects of the technological process of pottery production including: raw materials acquisition, preparation of clay paste, forming and firing of Tartessian vessels in the Early Iron Age. The land of Tartessos, now the Lower Guadalquivir region in western Andalusia, was deeply influenced by the newcomers from the Eastern Mediterranean (Celestino and López-Ruiz, 2016). For scholars who specialise in the archaeology of the Tartessian region, it is common to deal with ceramic vessels which were made by two different techniques: hand-made and wheel-thrown. One of the key sites of that land is Setefilla (See Fig. 1) excavated by George Edward Bonsor in the 1920’s (Bonsor and Thouvenot, 1928) and by María Eugenia Aubet, who carried out several archaeological campaigns in the 1970’s (e.g. Aubet 1975; 1978). This paper makes an attempt to examine the Tartessian ceramics not from a traditional typological posture seeking the chronological sequences, but from an uncommon approach, where experiment plays an important role. The goal is to shed light on these still relatively weakly recognised aspects of the study of the pottery from the South-western part of Iberian Peninsula. At the beginning of the Iron Age there was a marked advance in technological knowledge, a process which is particularly visible in the pottery production.